2D and 3D visualization of aquifer sediments, surface water seepage and groundwater flow using DC-resistivity, DC-IP, and SP methods, West El-Minia, Egypt - Ammar, A. I.; Kamal, K. A.; El-Boghdady, M. F. M.; Ebrahem, O. (Environmental earth sciences, 2023)
In this study, the SP, DC-Resistivity and DC-TDIP methods were used and included 21 sites for determining the groundwater conditions and visualizing the aquifer sediments, surface water seepage, and groundwater flow in 2D and 3D. The results indicated the occurrence of Quaternary and Tertiary deposits, as well as shallow aquifer of Eocene fractured limestone and Quaternary deposits. The resistivity, chargeability and SP values were compared with each other and 2D and 3D visualization models were designed for these values to understand the sediment distribution and its geological and hydrogeological implications. High to medium, low and very low chargeability values indicated the compact sediments with high shale content, water-bearing layers and freshwater zones and dry sediments, respectively, and varied with the water amount, salinity and effective porosity. Low to very low values of SP indicated the occurrence and high accumulation of groundwater and an increase in shale, permeability and groundwater flow and source, and possibly salinity. The results showed that the resistivity, chargeability and SP values had an important role in separating the dry and saturated sediments and defining the fault zone, determining the source of surface water seepage, classifying the depths of high, medium and low groundwater accumulation and flow and permeability. The IP depended highly on the water amount and shale content and it was interesting in groundwater exploration with resistivity and in differentiating between groundwater and clays. The SP assisted in delineating the surface water seepage and groundwater source and flow direction, and predicting the sediments permeability.